Delirium after hip hemiarthroplasty for proximal femoral fractures in elderly patients: risk factors and clinical outcomes - de Jong L (Dove Medical Press, 2019)
Louis de Jong,1 Veronique AJIM van Rijckevorsel,1 Jelle W Raats,1 Taco MAL Klem,2 Tjallingius M Kuijper,3 Gert R Roukema11Surgery Department, Maasstad Hospital, 3079 DZ Rotterdam, the Netherlands; 2Surgery Department, Franciscus Hospital, 3045 PM Rotterdam, the Netherlands; 3Science Board, Maasstad Hospital, 3079 DZ Rotterdam, the NetherlandsBackground: The primary aim of the present study was to verify the potential risk factors for developing a delirium after hip fracture surgery. The secondary aim of this study was to examine the related clinical outcomes after a delirium developed post-hip fracture surgery.Patients and methods: Data were extracted from a prospective hip fracture database and completed by retrospective review of the hospital records. A total of 463 patients undergoing hip fracture (hip hemiarthroplasty) surgery in a level II trauma teaching hospital between January 2011 and May 2016 were included. Delirium was measured using the Delirium Observation Screening Scale, the confusion assessment method, and an observatory judgment by geriatric medicine specialists.Results: The results showed that 26% of the patients (n=121) developed a delirium during hospital stay with a median duration during admission of 5 days (IQR 3–7). The multivariable model showed that the development of delirium was significantly explained by dementia (OR 2.75, P=0.001), age (OR 1.06, P=0.005), and an infection during admission (pneumonia, deep surgical site infection, or urinary tract infection) (OR 1.23, P=0.046). After 1 year of follow-up, patients who developed delirium after hip fracture surgery were significantly more discharged to (semi-independent) nursing homes (P<0.001) and had a significantly higher mortality rate (P<0.001) compared to patients without delirium after hip fracture surgery.Conclusions: The results showed that 26% of the patients undergoing hip fracture surgery developed a delirium. The risk factors including age, dementia, and infection during admission significantly predicted the development of the delirium. No association was confirmed between delirium and time of admission or time to surgery. The development of delirium after hip fracture surgery was subsequently found to be a significant predictor of admission to a nursing home and mortality after 1 year.Keywords: delirium, hip fracture, femoral neck fracture, mortality, risk and prognostic factors, hemi athroplasty, fragile